Problematika Pengawasan Guru Agama Hindu Dalam Peningkatkan Mutu Pendidikan Di Kementerian Agama Kota Denpasar - Temon Astawa, I Nyoman (LPM IHDN Denpasar, 2019)
The Implementation of the Supervision of Hindu Religious Education is an act done by the Supervisors of Hindu Religious Education in order to be able to achieve the established goals, one of the aims is to improve the performance of Hindu Religious Education Teachers in improving the quality of education.Supervision in improving the performance of Hindu Religious Education Teachers in an effort to improve the quality of education is inseparable from the existence of an action to achieve the goal by utilizing the existing elements. In the supervisory action conducted by the Supervisor of Hindu Education on Hindu Religious Education Teachers, there are factors that hinder the implementation of the Hindu Religious Education Supervisory strategy. Inhibiting factors may arise from the Supervisors of Hindu Religious Education, Hindu Religious Education Teachers, as well as from the policy of supervisors.